Learning motivation, learning environment, and motor ability in physical education outcomes: a systematic review - Darliani Darliani; Anton Komaini; Wilda Welis; Rika Sepriani (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
Physical Education, Sports, and Health (PJOK) learning in elementary schools is influenced by students’ learning motivation, learning environment, and motor ability. This study employed a systematic review design following PRISMA 2020 guidelines to synthesize 10 national and international studies published between 2018 and 2025, with inclusion criteria: elementary school participants, PJOK-focused outcomes, and quantitative, qualitative, or mixed-method designs. Findings indicate that intrinsic motivation enhances student participation, persistence, and readiness; supportive learning environments improve engagement, comfort, and opportunities for meaningful practice; and motor ability serves as a fundamental prerequisite for mastering movement skills. The integration of these factors highlights the need for a comprehensive approach addressing psychological, environmental, and motor-development aspects. These findings provide an evidence-based foundation for developing more effective, developmentally appropriate PJOK instructional strategies.